Smart grid : applications, communications, and security. - Berger, Lars Torsten, ....-; Iniewski, Krzysztof, ....- (Hoboken : Wiley, 2012)
Smart grids represent what many believe to be the next big technological revolution since the internet. Governments are pumping large sums of money into smart grid research, development and deployments. With the potential to reduce carbon dioxide emissions, increase reliability of electricity supply, and increase the efficiency of our energy infrastructure, it is clear that the advancement of these smart grids is an important and inevitable conclusion. This text will provide insight into the power electronics sensing, monitoring and control technologies, as well as deeply exploring the communication aspects of smart grids.